Hubungan antara curah hujan, penggunaan lahan dan karakteristik sungai di brantas hulu=The Relationship between Stream Discharge of River Catchment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK The aims of this research were to obtain the rating curve and the relationship between the stream discharge with rainfall, landuse and rivers' characteristics and to obtain the rivers stream discharge equations. The data were analysed using Stepwise Regression and the results showed that: (1) 28 percent of existing forest in the river catchment caused a continuous river stream discharge in one year, (2) if the sornnh cover 11,5 percent of the river catchment will decrease the fluctuation of stream discharge, and (3) major factors of the rainfall, landuse and rivers' characteristics that influenced the river catchment stream discharge were settlement, river slope, catchment area, rainfall and dry crops area.